Basic Model of Arabic Speaking for Preschool Children (Q-Nutqi) - Norfaezah Mohd Hamidin (Proceeding of International Conference on Islamic Education, 2021)
The Arabic language is the most important language in Malaysian education because of its connection with the Quranic language. This study is about the development of a basic model for improving the speaking skills of preschool children (Q-Nutqi). Q stands for Qur’an, Nutqi means to speak. The objectives of this study were to identify the basic needs in Arabic speaking skills of preschool children, then design and develop a model through the implementation of Arabic speaking modules of Quranic communication, finally, evaluate the effectiveness of this model. This study will be conducted using the ADDIE model. The analysis phase will identify the need for a basic model in speaking through the method of interviewing several Islamic preschool teachers in Selangor. Then, the model design phase to find out the learning objectives and determine the learning and teaching methods (L&T) using the Q-Nutqi model. The model development phase involves 12 experts in Arabic, early childhood education, and industry to evaluate the design of the model produced for improvement. The implementation phase of the Q-Nutqi speaking model through training modules for preschool teachers to use the model. The final phase is the evaluation phase to find out the impact and effectiveness of the model on preschool children. Through this study, the research team hopes to be able to develop a model that fits the basic needs of Arabic language learning of preschool children and be able to improve the existing weaknesses in the preschool education system.